High-Frequency Radiowave Probing of the High-Latitude Ionosphere - Greenwald, Raymond A (1985)
During the past several years, a program of high-frequency radiowave studies of the high latitude ionosphere has been developed. Studies are now being conducted on the formation and motion of high-latitude ionospheric electron density irregularities, using a sophisticated high-frequency radar system installed at Goose Bay, Labrador. The radar antenna is also being used to receive signals from a beacon transmitter located at Thule, Greenland. This information is providing a better understanding of the spatial and temporal variability of high-latitude propagation channels and their relationship to disturbances in the magnetosphere ionosphere system. Pub. in John Hopkins APL Technical Digest, v6 n1 p38-50 1985. Original contains color plates: All DTIC/NTIS reproductions will be in black and white.